Efficacy of valproate versus lithium in mania or mixed mania: a randomized, open 12-week trial - Bowden, C.L.; Mosolov, S.; Hranov, L.; Chen, E.; Habil, H.; Kongsakon, R.; Manfredi, R.; Lin, H.N. (2010)
The objective of this study was to compare the efficacy and safety of valproate and lithium in bipolar I patients experiencing a manic or a mixed episode. This international, randomized, open-label, parallel-group, equivalence study included 268 patients with bipolar I disorder. The starting dose of valproate was 20 mg/kg/day and that of lithium was 800 mg/day. Treatment duration was 12 weeks. The primary outcome measure was mean change in Young Mania Rating Scale score between baseline and study end. Secondary outcome measures were response and remission rates, change in Montgomery and Asberg Depression Rating Scale and Clinical Global Impression Bipolar Disorder instrument score, and occurrence of adverse events. The mean change from baseline in Young Mania Rating Scale score was 15.8 +/- 5.3 in the lithium group and 17.3 +/- 9.4 in the valproate group. The 90 confidence interval of the intergroup difference (-0.69; 3.31) was within prespecified equivalence limits. Response rates were 72.6 in the lithium group and 79.5 in the valproate group. Remission rates were 58.5 and 71.9, respectively. No intergroup differences were observed in median time to treatment response (21 days) or change in Clinical Global Impression Bipolar Disorder instrument or Montgomery and Asberg Depression Rating Scale scores. Adverse events were reported in 42.8 of patients in the lithium group and 41.5 in the valproate group. Valproate and lithium showed comparable efficacy and tolerability in the treatment of acute mania over 12 weeks. Int Clin Psychopharmacol 25: 60-67 (C) 2010 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.